Hubungan Pengetahuan, Sikap dan Perilaku Penggunaan Alat Pelindung Diri dengan Kejadian Kecelakaan Kerja pada Pekerja Bangunan di PT. XYZ Kota Depok: The Relationship Between Knowledge, Attitudes, and Practices of Personal Protective Equipment Use and the Incidence of Work Accidents Among Construction Workers - Putri Mustafa, Maulidya; Mustopa, Mustopa; Pujiati, Purwani (MPI Press, 2025)
Introduction: The occurrence of work accidents is caused by lack of supervision and lack of implementation of Occupational Safety and health in terms of the use of personal protective equipment. Objectives: The purpose of this study was to determine the relationship of knowledge, attitudes and behaviors of the use of personal protective equipment with the incidence of accidents at work in construction workers at PT. XYZ Depok City In 2024. Method: This study uses a quantitative research type with a cross-sectional design with a total of 50 respondents of construction workers at PT. XYZ. The sampling technique used is total sampling. the data used are primary data through questionnaires. Data analysis was carried out univariately and bivariately with the chi-square test. Result: Based on the research results, the knowledge variable from the statistical test results obtained a value (p = 0.000 < 0.05) with an OR of 0.048, the attitude variable from the statistical test results obtained a value of p = 0.003 < 0.05) with an OR of 0.016, the behavior variable from the statistical test results obtained a value (p = 0.001 < 0.05) with an OR of 0.013. Conclution: There is a relationship between knowledge, attitudes and behavior of using personal protective equipment with the occurrence of work accidents in construction workers at PT. XYZ, Depok City in 2024.